2017
DOI: 10.1080/17453674.2017.1290479
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of early and medium-term revision after post-fracture total knee arthroplasty

Abstract: Background and purposeTotal knee arthroplasty (TKA) due to posttraumatic fracture osteoarthritis (PTFA) may be associated with inferior prosthesis survival. This study is the first registry-based study solely addressing this issue. Both indications and predictors for revision were identified.Patients and methods52,518 primary TKAs performed between 1997 and 2013 were retrieved from the Danish Knee Arthroplasty Register (DKR). 1,421 TKAs were inserted due to PTFA and 51,097 due to primary osteoarthritis (OA). S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
31
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 35 publications
2
31
0
4
Order By: Relevance
“…47 It was 3% following tibial plateau fractures and 4% for displaced fractures treated by ORIF. Data from the Danish knee arthroplasty registry were published earlier this year, 48 confirming the same results after studying the outcomes of a larger scale of patients. The authors recalled the results of 1,421 TKAs that were implanted due to secondary OA.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…47 It was 3% following tibial plateau fractures and 4% for displaced fractures treated by ORIF. Data from the Danish knee arthroplasty registry were published earlier this year, 48 confirming the same results after studying the outcomes of a larger scale of patients. The authors recalled the results of 1,421 TKAs that were implanted due to secondary OA.…”
Section: Discussionsupporting
confidence: 62%
“…The authors found an increased risk of early and medium-term revision of TKAs inserted after intra-articular fractures. 48 Our study has some limitations. This includes the limited number of patients reported.…”
Section: Discussionmentioning
confidence: 89%
“…reported that patients with previous fractures around the knee were more likely to experience surgical site complications and an increase in 90‐day readmission rate after conversion to TKA in contrast to patients with previous soft‐tissue injuries about the knee. El‐Galaly et al . reported an increased risk of early‐ and medium‐term TKA revision due to previous fractures of the distal femur and/or proximal tibia.…”
Section: Discussionmentioning
confidence: 99%
“…Ge et al 9 reported that patients with previous fractures around the knee were more likely to experience surgical site complications and an increase in 90-day readmission rate after conversion to TKA in contrast to patients with previous soft-tissue injuries about the knee. El-Galaly et al 10 reported an increased risk of early-and medium-term TKA revision due to previous fractures of the distal femur and/or proximal tibia. Houdek et al 1 found that patients with a previous distal femoral fracture were at increased risk for postoperative complications (HR 1.47) compared with patients who had a history of proximal tibial fracture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation